Hubungan antara Status Gizi dan Infeksi Blastocystis hominis pada Pasien Bangsal Anak RSUD Dr. Moewardi Surakarta - Nabila Adib Sungkar; Paramasari Dirgahayu; Annang Giri Moelyo (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background :Blastocystis hominis is one of the most common protozoans found in worldwide human intestinal tract. In Indonesia, its prevalence reached 60%, the highest prevalence found in children less than 6 years old (25%). Epidemiological and clinical researches show that a defect of nutritional status can inhibit immunity response and increase risk of infectional disease. This study aimed to analyze the correlation between nutritional status and Blastocystis hominis infection among children in RSUD Dr. Moewardi Surakarta. Methods :This study was an observational analytical research using cross-sectional approach. The subjects were every pediatric ward patient in RSUD Dr. Moewardi Surakarta period July-August 2013. A total of 50 subjects were selected using total sampling method. Fresh stool samples were examined using Ziehl-Neelsen staining method. Data were analyzed by multiple logistic regression analysis and processed with the Statistical Product and Service Solutions (SPSS) 17.0 for Windows. Results :Blastocystis hominis was found in 36/50 (72%) stool samples. Poor nutritional status patients in pediatric ward of RSUD Dr. Moewardi Surakarta have the same risk to be infected by Blastocystis hominis compared to good nutritional status patients (OR = 1.04 ; p < 0.97). But children aged under 2 years old have lower risk to get infected by Blastocystis hominis compared to children over 2 years old (OR = 29,333 ; p < 0,001) Conclusion :There is not any significant correlation between nutritional status and Blastocystis hominis infection among children in RSUD Dr. Moewardi Surakarta. Keywords :Blastocystis hominis, nutritional status